Some network-type properties of the space of G-permutation degree - Lj. D.R Kočinac; F. G. Mukhamadiev; A. K. Sadullaev; Sh. U. Meyliev (Applied General Topology, 2023)
In this paper the network-type properties (network,cs−network,cs∗−network,cn−network andck−network) of the spaceSPnGXofG-permutation degree ofXare studied. It is proved that:(1) IfXis aT1-space that has a network of cardinality≤κ, thenSPnGXhas a network of cardinality≤κ;(2) IfXis aT1-space that has acs-network (resp.cs∗-network) ofcardinality≤κ, thenSPnGXhas acs-network (resp.cs∗-network) ofcardinality≤κ;(3) IfXis aT1-space that has acn-network (resp.ck-network) ofcardinality≤κ, thenSPnGXhas acn-network (resp.ck−network) ofcardinality≤κ.